Pelatihan Multimedia Interaktif bagi Guru di Lingkungan Daerah Aliran Sungai (DAS) - Puspitasari, Sry Rita; Sasalia S, Putri; Demitra; Hamdani, Muhammad; Pinardi, Janu (Community Education Engagement Journal, 2024)
The Interactive Multimedia Training for Teachers in the Watershed Area aimed to enhance teachers' competencies in utilizing interactive multimedia technology in teaching. The training was designed to address educational challenges in watershed areas, which require innovative and relevant approaches in the teaching process. The training methods included both theoretical and practical sessions, with materials covering the introduction of multimedia software, techniques for creating interactive learning media, and the application of technology in the context of environmental education. The results of the training showed that participating teachers were also able to develop multimedia-based teaching materials that are more engaging and contextual for students. This initiative is expected to serve as a model for teacher competency development in other regions with similar geographical conditions, and contribute to the improvement of technology-based education quality in Indonesia, particularly in watershed areas. The training marks a significant initial step in supporting the integration of technology in education and environmental conservation efforts through contextual learning.